The apes - Wexo, John Bonnett; Schroeder, Charles Roy. (Mankato, Minn. Creative Education, 1990)
Discusses the physical description, habits, and behavior of the members of the ape family (gorillas, orangutans, chimpanzees), using numerous pictures.
Keywords: Apes -- Juvenile literature; Apes